Adhesive sheet and dimming device using same
By rationally formulating (meth)acrylate copolymer, crosslinking agent and specific ultraviolet absorber in the adhesive sheet, the problem of reduced appearance properties caused by ultraviolet absorbers in the prior art is solved, and efficient ultraviolet absorption and stability are achieved optical properties.
Patent Information
- Application Number
- CN202380031805.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-01
- Filing Date
- 2023-03-24
- Publication Date
- 2024-12-13
AI Technical Summary
The conventional adhesive sheet has the potential to reduce the appearance characteristics due to the influence of the ultraviolet absorber, and it is difficult to prevent the appearance quality from being reduced while maintaining sufficient ultraviolet absorbing performance.
Using an adhesive sheet containing (meth)acrylate copolymer, a crosslinking agent and specific UV absorbers A and B, the content of the UV absorber in 9 parts by weight of 100 parts by weight of the (meth)acrylate copolymer is controlled. The following and 3 parts by weight are ensured that the spectral transmittance is less than 25%, and the thickness is 50 to 200 μm. Combined with appropriate crosslinking agents and additives, an efficient adhesive sheet is formed.
It is achieved to provide sufficient ultraviolet absorption performance without reducing appearance quality, and by optimizing composition and structure, the reduction of appearance characteristics is suppressed, ensuring the stability and performance of optical functional components.
Smart Images

Figure CN119137230A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a pressure-sensitive adhesive sheet for an optical functional member and a light-adjusting device. Background Art
[0002] In recent years, various adhesive sheets have been developed for laminating cover films, electrode films, etc. constituting touch panel displays used in smartphones, etc., or for laminating dimming sheets used in dimming devices to glass plates. For example, Patent Document 1 discloses an adhesive sheet having ultraviolet absorption properties for laminating dimming sheets.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2016-180985 Summary of the invention
[0006] Problems to be solved by the invention
[0007] However, such adhesive sheets have the potential to reduce appearance properties such as white turbidity due to the influence of the ultraviolet absorber. The present invention is made to solve the above problems, and its purpose is to provide an adhesive sheet having sufficient ultraviolet absorption performance and capable of suppressing the reduction of appearance properties, and a dimming device using the adhesive sheet.
[0008] Solutions for solving problems
[0009] Item 1. A pressure-sensitive adhesive sheet, the pressure-sensitive adhesive sheet being a pressure-sensitive adhesive sheet for an optical functional member,
[0010] The adhesive sheet comprises: a (meth)acrylate copolymer as a main component, a crosslinking agent, and an ultraviolet absorber.
[0011] contains at least one of ultraviolet absorber A and ultraviolet absorber B as the ultraviolet absorber,
[0012] The content of the ultraviolet absorber A, when contained, is 9 parts by weight or less relative to 100 parts by weight of the (meth)acrylate copolymer.
[0013] The content of the ultraviolet absorber B, when contained, is 3 parts by weight or less relative to 100 parts by weight of the (meth)acrylate copolymer.
[0014] The ultraviolet absorber A contains a compound represented by formula (1), and the ultraviolet absorber B contains a compound represented by formula (2).
[0015] (In the formula, R1, R4, and R5 represent lower alkyl groups having 1 to 6 carbon atoms, R2 represents lower alkylene groups having 1 to 6 carbon atoms, and R3 represents an alkyl group having 5 to 15 carbon atoms)
[0016] [Chemical formula 1]
[0017]
[0018] [Chemical formula 2]
[0019]
[0020] Item 2. The pressure-sensitive adhesive sheet according to Item 1, comprising both the ultraviolet absorber A and the ultraviolet absorber B as the ultraviolet absorber.
[0021] Item 3. The adhesive sheet according to Item 1, wherein the content of the ultraviolet absorber A is 6 parts by weight or less, and the content of the ultraviolet absorber B is 2 parts by weight or less, based on 100 parts by weight of the (meth)acrylate copolymer.
[0022] Item 4. The pressure-sensitive adhesive sheet according to any one of Items 1 to 3, wherein the pressure-sensitive adhesive sheet has a spectral transmittance of 25% or less for light having a wavelength of 400 nm.
[0023] Item 5. The pressure-sensitive adhesive sheet according to any one of Items 1 to 4, wherein the thickness is 50 to 200 μm.
[0024] Item 6. A dimming device comprising: a glass plate; a dimming sheet; and the adhesive sheet according to any one of Items 1 to 5, for fixing the dimming sheet to the glass plate.
[0025] Beneficial Effects
[0026] According to the pressure-sensitive adhesive sheet of the present invention, it is possible to have sufficient ultraviolet absorption performance while suppressing the deterioration of appearance. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a cross-sectional view of a pressure-sensitive adhesive sheet laminate according to one embodiment of the present invention. DETAILED DESCRIPTION
[0028] Hereinafter, an embodiment of the adhesive sheet of the present invention is described. The adhesive sheet is an adhesive sheet for installing optical functional components such as a dimming sheet, a cover sheet, and an electrode film. For example, the dimming sheet can be fixed on a glass plate by the adhesive sheet. Alternatively, it can be used for an electrostatic capacitive touch panel display, and the adhesive sheet can be pasted on one surface of a transparent electrode film constituting the touch panel, and the electrode film can be pasted on a display such as a liquid crystal through the adhesive sheet. It should be noted that the above-mentioned use is an example, and it can be used for optical functional components for various purposes.
[0029] The pressure-sensitive adhesive sheet contains a (meth)acrylate copolymer, a crosslinking agent, and an ultraviolet absorber as main components, which are described in detail below.
[0030] <1. (Meth)acrylate copolymer>
[0031] The (meth)acrylate polymer constitutes the main component of the adhesive composition forming the adhesive sheet. The proportion of the acrylate copolymer in the adhesive sheet is not particularly limited, but is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 99% by mass or more.
[0032] From the viewpoint of suppressing the generation of bubbles caused by waste gas from the adherend even when the adhesive sheet is exposed to a high temperature environment in a state of close contact with the adherend, and from the viewpoint of peeling of the adherend, the acrylate copolymer is preferably a copolymer of an alkyl (meth)acrylate and a monomer having a reactive functional group. It should be noted that the acrylate copolymer in the adhesive composition may be one or more. In addition, the acrylate copolymer may also be used in combination with other polymers.
[0033] As the alkyl (meth)acrylate, preferably methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, tetradecyl (meth)acrylate, hexadecyl (meth)acrylate, octadecyl (meth)acrylate, etc. can be listed. Only one kind of alkyl (meth)acrylate can be used, or two or more kinds can be mixed and used. It should be noted that in this specification, "(meth)acrylic acid" refers to "acrylic acid" or "methacrylic acid".
[0034] In addition, as monomers with reactive functional groups, monomers containing hydroxyl groups, monomers containing amino groups, etc. can be listed. From the perspective of not easily corroding metals such as transparent conductive films, and then in the case of being exposed to a high temperature environment in a state where the adhesive sheet is in close contact with the adherend, the generation of bubbles caused by waste gas from the adherend is also suppressed, and from the perspective of peeling of the adherend, monomers containing hydroxyl groups are preferably considered. As monomers containing hydroxyl groups, 2-hydroxyethyl (meth) acrylate, 2-hydroxypropyl (meth) acrylate, 3-hydroxypropyl (meth) acrylate, 2-hydroxybutyl (meth) acrylate, 3-hydroxybutyl (meth) acrylate, 4-hydroxybutyl (meth) acrylate, etc. (meth) acrylate hydroxyalkyl esters, etc. can be preferably listed. Hydroxyl-containing monomers can be used only one, or two or more can be mixed and used.
[0035] The hydroxyl value of the acrylic acid ester copolymer is not particularly limited, but from the viewpoint of suppressing the generation of bubbles due to offgas from the adherend even when the pressure-sensitive adhesive sheet is exposed to a high temperature environment in a state of being in close contact with the adherend and preventing peeling of the adherend, the lower limit is preferably 5 mgKOH / g or more, more preferably 10 mgKOH / g or more, and the upper limit is preferably 100 mgKOH / g or less, more preferably 90 mgKOH / g or less.
[0036] In addition, as the weight average molecular weight of the acrylate copolymer, there is no particular restriction. From the perspective of suppressing the generation of bubbles caused by the waste gas from the adherend even when the adhesive sheet is exposed to a high temperature environment in a state of close contact with the adherend, and from the perspective of peeling of the adherend, the lower limit can be preferably 300,000 or more, more preferably 500,000 or more, more preferably 700,000 or more, and particularly preferably 750,000 or more, and the upper limit can be preferably 1.2 million or less, more preferably 1 million or less, more preferably 900,000 or less, particularly preferably 850,000 or less, particularly preferably 750,000 to 900,000, 750,000 to 850,000. It should be noted that the weight average molecular weight of the acrylate copolymer (a) is a value converted to polystyrene measured by gel permeation chromatography (GPC). As the acrylate copolymer, a commercially available acrylate copolymer can be used, and an acrylate copolymer synthesized by a known method can also be used.
[0037] <2. Cross-linking agent>
[0038] As long as the cross-linking agent plays the function of making the (meth) acrylate copolymer cross-linked, there is no particular limitation. For example, it can be selected from known cross-linking agents such as isocyanate compounds, epoxy compounds, oxazoline compounds, aziridine compounds, metal chelate compounds, butylated melamine compounds, etc., considering the reactivity with the cross-linking functional group possessed by the (meth) acrylate copolymer. For example, when the (meth) acrylate copolymer has a hydroxyl group as a cross-linking functional group, it is preferred to use an isocyanate compound or a metal chelate compound from the aspect of good cross-linking reactivity with the hydroxyl group. The cross-linking agent can be used only one, or two or more can be used in combination. For example, an isocyanate compound and a metal chelate compound can be mixed.
[0039] As the crosslinking agent, isocyanate compounds and metal chelate compounds are preferred from the viewpoint of being able to appropriately crosslink the (meth)acrylate copolymer. Examples of the isocyanate compound include tolylene diisocyanate, xylene diisocyanate, hexamethylene diisocyanate, and isophorone diisocyanate.
[0040] Examples of the metal chelate compound include compounds in which a polyvalent metal such as aluminum, iron, zinc, tin, titanium, antimony, magnesium, or vanadium is coordinated to acetylacetone or ethyl acetoacetate. These compounds may be used alone or in combination of two or more.
[0041] The content of the crosslinking agent is not particularly limited, but from the viewpoint of suppressing peeling, the lower limit is preferably 0.001 parts by weight or more, more preferably 0.01 parts by weight or more, and the upper limit is preferably 5.0 parts by weight or less, more preferably 3.0 parts by weight or less, relative to 100 parts by weight of the (meth)acrylate copolymer.
[0042] When using isocyanate compounds as crosslinking agents, if the content is too much, there is a hidden danger that the adhesive sheet hardens and the bonding strength decreases, so it is preferably below 1.0 weight part. In addition, when using metal chelate compounds, if the content is too much, the b* value is likely to increase, so it is preferably below 0.5 weight part, more preferably below 0.3 weight part, and particularly preferably below 0.1 weight part.
[0043] <3. Ultraviolet light absorber>
[0044] The pressure-sensitive adhesive sheet of the present embodiment contains at least one of the ultraviolet absorber A and the ultraviolet absorber B as the ultraviolet absorber.
[0045] The ultraviolet absorber A contains a halogen group and is liquid at 20°C. As such an ultraviolet absorber A, for example, a compound represented by the following formula (1) may be contained (in the formula (1), R1 represents a lower alkyl group having 1 to 6 carbon atoms, R2 represents a lower alkylene group having 1 to 6 carbon atoms, and R3 represents an alkyl group having 5 to 15 carbon atoms). Specifically, as the ultraviolet absorber A, for example, a liquid benzotriazole ultraviolet absorber having a chlorine atom as a functional group may be used.
[0046] [Chemical formula 3]
[0047]
[0048] The ultraviolet absorber B contains a halogen group and is in powder form at room temperature (20°C). Such an ultraviolet absorber A, for example, contains a compound represented by the following formula (2) (in formula (2), R4 and R5 represent a lower alkyl group having 1 to 6 carbon atoms). Specifically, as the ultraviolet absorber B, for example, a powdered benzotriazole ultraviolet absorber having a chlorine atom as a functional group can be used.
[0049] [Chemical formula 4]
[0050]
[0051] The ultraviolet light absorbing effect of the ultraviolet light absorber B is high, but if the content of the ultraviolet light absorber B is high, it is likely to precipitate on the surface of the adhesive sheet. On the other hand, if the ultraviolet light absorber A is contained too much, the haze rate of the adhesive sheet is likely to increase. In addition, if the content of any ultraviolet light absorber is low, the ultraviolet light absorbing effect is reduced.
[0052] From these viewpoints, the content of the ultraviolet absorber A is 9 parts by weight or less, preferably 7 parts by weight or less, and more preferably 5 parts by weight or less, relative to 100 parts by weight of the (meth)acrylate copolymer. On the other hand, the lower limit is preferably 1 part by weight or more, and more preferably 3 parts by weight or more.
[0053] On the other hand, the content of the ultraviolet absorber B is 3 parts by weight or less, preferably 2 parts by weight or less, and more preferably 1.5 parts by weight or less, based on 100 parts by weight of the (meth)acrylate copolymer. On the other hand, the lower limit is preferably 0.5 parts by weight or more, and more preferably 1 part by weight or more.
[0054] Therefore, as the ultraviolet absorber, only one of the ultraviolet absorbers A and B may be used, but it is preferred that both are contained in a good balance.
[0055] <4. Additives>
[0056] In the adhesive composition, various additives commonly used in acrylic adhesives may be added as needed, such as silane coupling agents, ultraviolet absorbers, antistatic agents, tackifiers, antioxidants, light stabilizers, softeners, fillers, refractive index adjusters, etc. It should be noted that the polymerization solvent and dilution solvent described below are not included in the additives constituting the adhesive composition.
[0057] <5. Thickness of adhesive sheet>
[0058] The thickness of the adhesive sheet is preferably 10 to 300 μm, more preferably 12 to 280 μm, and particularly preferably 15 to 250 μm. The reason is that if the thickness is small, the mounted components such as the dimming sheet may be easily peeled off. On the other hand, if the thickness becomes large, the productivity and the cutting property of the adhesive sheet may be reduced. In addition, the total light transmittance and b* value may also become higher.
[0059] <6. Optical properties of adhesive sheet>
[0060] The optical properties of the adhesive sheet of this embodiment are preferably as follows. It should be noted that in the following optical properties, the total light transmittance, haze rate and chromaticity are measured for a laminated body formed by sequentially laminating a plain glass plate with a thickness of 0.7 mm, an adhesive sheet and a PET sheet with a thickness of 50 μm (A430050 manufactured by Toyobo Co., Ltd.). In addition, the color difference ΔE before and after ultraviolet irradiation is measured for a laminated body formed by sequentially laminating a plain glass plate with a thickness of 0.7 mm, an adhesive sheet and a dimming sheet.
[0061] The total light transmittance based on JIS K7136-1 is preferably 80% or more, more preferably 85% or more, particularly preferably 90% or more.
[0062] The haze rate based on JIS K7136 is preferably 5% or less, more preferably 2% or less, and particularly preferably 1% or less.
[0063] In the L*, a*, b* colorimetric system (CIE standard), the chromaticity b* is preferably 5 or less, more preferably 4 or less, and particularly preferably 3 or more.
[0064] Regarding ultraviolet absorption performance, the spectral transmittance for light of 400 nm wavelength is preferably 25% or less, more preferably 20% or less, and particularly preferably 15% or less. Furthermore, the spectral transmittance for light of 420 nm wavelength is preferably 70% or more.
[0065] In addition, the color difference ΔE before and after ultraviolet irradiation is preferably 1.0 or less, and more preferably 0.5 or less. The color difference ΔE can be calculated as follows. That is, the differences in chromaticity L*, chromaticity a*, and chromaticity b* before and after ultraviolet irradiation are calculated as ΔL*, Δa*, and Δb*, respectively, and the color difference ΔE is calculated using the following formula.
[0066] [Mathematical formula 1]
[0067]
[0068] The integrated light amount of ultraviolet light when calculating the above ΔL*, Δa*, and Δb* can be set to, for example, 10000 mJ / cm 2 , or set to 80000mJ / cm 2 If ΔE exceeds 1.0, a change in color may be visually observed, which is not preferable.
[0069] <7. Adhesive properties of adhesive sheets>
[0070] The adhesive performance of the adhesive sheet of the present embodiment is preferably 10 N / 25 mm or more, and more preferably 15 N / 25 mm or more. The measuring method will be described later.
[0071] <8. Method for producing adhesive sheet>
[0072] The method for producing the pressure-sensitive adhesive sheet of the present embodiment is not particularly limited, and can be carried out, for example, as follows.
[0073] First, a (meth)acrylate polymer, a crosslinking agent, a UV absorber, a diluting solvent or a curing retarder, and the above-mentioned additives as necessary are prepared.
[0074] The (meth)acrylate polymer can be produced by polymerizing a mixture of monomers constituting the polymer by a conventional free radical polymerization method. The polymerization of the (meth)acrylate polymer is preferably carried out by a solution polymerization method using a polymerization initiator as required. Examples of the polymerization solvent include ethyl acetate, n-butyl acetate, isobutyl acetate, toluene, acetone, hexane, methyl ethyl ketone, and the like, and two or more thereof may be used in combination.
[0075] Examples of the polymerization initiator include azo compounds and organic peroxides, and two or more thereof may be used in combination. Examples of the azo compounds include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane 1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), 2,2'-azobis(2-methylpropionic acid methyl ester), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-hydroxymethylpropionitrile), and 2,2'-azobis[2-(2-imidazolin-2-yl)propane].
[0076] Examples of the organic peroxide include benzoyl peroxide, tert-butyl perbenzoate, cumene hydroperoxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethoxyethyl) peroxydicarbonate, tert-butyl peroxyneodecanoate, tert-butyl peroxypivalate, (3,5,5-trimethylhexanoyl) peroxide, dipropionyl peroxide, and diacetyl peroxide.
[0077] In addition, in the above-mentioned polymerization step, by adding a chain transfer agent such as 2-mercaptoethanol, the weight average molecular weight of the obtained polymer can be adjusted.
[0078] After obtaining the (meth)acrylate polymer, a crosslinking agent, a UV absorber and a diluting solvent (or a curing retardant) are added to the (meth)acrylate polymer solution, and the above additives are mixed as needed to obtain a pressure-sensitive adhesive composition (coating liquid) diluted with a solvent.
[0079] It should be noted that, among any of the above-mentioned components, when a solid component is used, or when precipitation occurs when mixed with other components in an undiluted state, the component can be dissolved or diluted in a diluting solvent in advance and then mixed with other components.
[0080] As the above-mentioned dilution solvent, for example, aliphatic hydrocarbons such as hexane, heptane, and cyclohexane, aromatic hydrocarbons such as toluene and xylene, halogenated hydrocarbons such as dichloromethane and vinyl chloride, alcohols such as methanol, ethanol, propanol, butanol, and 1-methoxy-2-propanol, ketones such as acetylacetone, methyl ethyl ketone, 2-pentanone, isophorone, and cyclohexanone, esters such as ethyl acetate and butyl acetate, and cellosolve-based solvents such as ethyl cellosolve can be used.
[0081] The concentration and viscosity of the coating solution prepared in this way can be appropriately selected according to the situation as long as it is within the range that can be applied. For example, the concentration of the adhesive composition can be diluted to 10 to 60% by mass. It should be noted that when obtaining the coating solution, the addition of a diluting solvent or the like is not a necessary condition, and as long as the adhesive composition is a viscosity that can be applied, a diluting solvent may not be added. In this case, the coating solution becomes a coating solution in which the polymerization solvent of the (meth)acrylate polymer is directly used as a diluting solvent.
[0082] Then, the coating solution prepared as described above is coated on, for example, a peeling substrate sheet, etc., and the coating solution is crosslinked, so that an adhesive layer (adhesive sheet) can be formed to manufacture. As a crosslinking method, heating and drying can be listed. By heating the adhesive composition, the crosslinking agent crosslinks the (methyl) acrylate copolymer to each other, and the adhesive layer can be made into a solidified, semi-cured state. It should be noted that, as the coating method of the coating solution, it is possible to appropriately select from the known coating methods such as a knife coater, a micro-rod coater, an air knife coater, a reverse roll coater, a reverse gravure coater, a variable speed gravure coater, a die coater, a curtain coater, etc.
[0083] The heating temperature of the heat treatment during crosslinking is preferably 50 to 150° C., more preferably 80 to 120° C. In addition, the heating time is, for example, preferably 10 seconds to 10 minutes, more preferably 50 seconds to 2 minutes. It should be noted that if the heating temperature is low, the ultraviolet absorber may precipitate or the adhesive force may decrease, so the heating temperature is preferably high.
[0084] After the heat treatment, a curing period of about 1 to 2 weeks may be provided at room temperature (e.g., 23° C., 50% RH) as required. If such a curing period is required, the adhesive sheet is formed after the curing period. On the other hand, if a curing period is not required, the adhesive sheet is formed after the heat treatment is completed.
[0085] Through the above-mentioned heat treatment (and curing), the (meth)acrylate polymer is fully cross-linked by the cross-linking agent to form a cross-linked structure, thereby obtaining a pressure-sensitive adhesive sheet.
[0086] <9. Adhesive Sheet Laminate>
[0087] Next, the adhesive sheet laminate of this embodiment is described. Figure 1 As shown, the adhesive sheet laminate of this embodiment includes a first release sheet 1, an adhesive layer 2 laminated on the first release sheet 1, and a second release sheet 3 disposed on the adhesive layer 2. The first release sheet 1 and the second release sheet 3 are well-known release sheets, and at least one of them has a release surface.
[0088] The adhesive sheet laminate can be manufactured, for example, as follows. First, the first release sheet 1 is unwound from a unwinding roller on which the first release sheet 1 is wound. Then, a coating liquid of the above-mentioned adhesive composition is applied to the release surface of the first release sheet 1, and a heat treatment is performed to thermally crosslink the adhesive composition, thereby forming an adhesive layer 2. The adhesive layer 2 is equivalent to the adhesive sheet of the present invention. Then, a second release sheet 3 is attached in a manner covering the adhesive layer 2. At this time, the release surface of the second release sheet 3 is brought into contact with the adhesive layer 2. In this way, a laminate as shown in FIG. Figure 1 The adhesive sheet laminate shown.
[0089] <10. Features>
[0090] Since the pressure-sensitive adhesive sheet of the present invention contains at least one of the halogen group-containing ultraviolet absorber A and the ultraviolet absorber B as the ultraviolet absorber, high ultraviolet absorption performance can be obtained.
[0091] Example
[0092] Hereinafter, examples of the present invention will be described. However, the present disclosure is not limited to the examples shown below.
[0093] <1. Preparation of Examples and Comparative Examples>
[0094] According to the production method described below, pressure-sensitive adhesive sheets of Examples 1 to 5 and Comparative Examples 1 to 5 were prepared.
[0095] The compositions of the materials used in the adhesive sheets of Examples 1 to 5 and Comparative Examples 1 to 5 are shown in Tables 1 and 2. The details of the materials shown in the tables are as follows, and the materials were diluted with a solvent such as ethyl acetate as necessary before use.
[0096] Acrylate polymer: weight average molecular weight 800,000 to 900,000, hydroxyl value 27 mgKOH / g.
[0097] Isocyanate compound: BXX4773 manufactured by Toyo Ink Co., Ltd.
[0098] Metal chelate compound: EXK18-223 manufactured by Toyo Ink Co., Ltd.
[0099] Halogen group-containing liquid ultraviolet absorber A: EVERSORB 109 manufactured by Everlight Chemical Industrial Corporation (maximum absorption wavelength: 353 nm).
[0100] Halogen group-containing powdery ultraviolet absorber B: Tinuvin 326 manufactured by BASF Japan (maximum absorption wavelength: 353 nm).
[0101] Halogen-free ultraviolet absorber C: Tinuvin 384-2 manufactured by BASF Japan.
[0102] Benzophenone-based ultraviolet absorber: Tinuvin 477 manufactured by BASF Japan.
[0103] [Table 1]
[0104]
[0105] [Table 2]
[0106]
[0107] Use an applicator to apply the coating liquid for Examples 1 to 5 and Comparative Examples 1 to 5 prepared as described above onto an A4-sized first release sheet (manufactured by Fujimori Industries, Ltd., model number: 50E0010-DG2) to form an adhesive layer on the first release sheet. Next, heat / dry the substrate sheet in a drying oven (manufactured by ADVANTEC, model number: DRD620DA) at 105°C for 7 minutes to cure the adhesive layer. In this way, adhesive sheets of Examples 1 to 5 and Comparative Examples 1 to 5 are generated on the first release sheet. Then, a second release sheet (manufactured by Fujimori Industries, Ltd., model number: 50E0010-BD) is attached to each adhesive sheet to produce the following: Figure 1 The thickness of the adhesive sheet of Examples 1, 3 to 5, and Comparative Examples 1 to 5 was 100 μm in the cured state, and the thickness of the adhesive sheet of Example 2 was 120 μm in the cured state.
[0108] Next, the following measurements were performed on the pressure-sensitive adhesive sheets of Examples 1 to 5 and Comparative Examples 1 to 5. The results are shown in Tables 3 and 4.
[0109] A. Total light transmittance, haze rate
[0110] For each adhesive sheet, the total light transmittance and haze were measured for a laminate having a layer structure of glass (thickness: 0.7 mm) / adhesive sheet / 50 μm PET film (manufactured by Toyobo Co., Ltd.) The total light transmittance was measured in accordance with JIS K7136-1, and the haze was measured in accordance with JIS K7136.
[0111] B. Chromaticity b*, spectral transmittance characteristics
[0112] The chromaticity b* and spectral transmittance characteristics were measured using a spectrophotometer (manufactured by Hitachi High-Technologies Corporation: U4100).
[0113] C. Adhesion test
[0114] The first release sheet was peeled off from each adhesive sheet laminate, and the exposed adhesive layer was bonded to a polyethylene terephthalate (PET) film (thickness: 25 μm) to obtain a laminate having a layer structure of second release sheet / adhesive layer / PET film. The obtained laminate was cut into pieces of 25 mm wide and 120 mm long to serve as a sample.
[0115] Next, the second peeling sheet was peeled off from the sample under the conditions of temperature 23°C and relative humidity 50%RH, and the exposed adhesive layer was pasted on a polyethylene terephthalate (PET) film (Toyobo Co., Ltd. model: A4300 thickness: 100μm) by rolling back and forth once with a 2kg roller, and then placed under the conditions of temperature 23°C and relative humidity 50%RH for 30 minutes. Next, a tensile tester was used to peel the interface between the PET film and the adhesive layer under the conditions of a peeling speed of 300mm / min and a peeling angle of 180°, and the adhesive force (N / 25mm) was measured to evaluate the adhesive force of the adhesive sheet. It should be noted that other conditions were measured in accordance with JISZ0237:2009.
[0116] D. Appearance
[0117] The appearance of the produced PSA sheet was visually inspected to confirm white turbidity, precipitation of materials, etc.
[0118] E. Chromatic aberration
[0119] The color difference ΔE before and after ultraviolet irradiation was measured for a laminated body composed of a 0.7 mm thick plain glass plate, an adhesive sheet, and a dimming sheet. The dimming sheet (HCLC-12 manufactured by Greentask Co. Ltd.) was formed by sandwiching a liquid crystal layer between a pair of 188 μm thick ITO films (GSA-A8A5 manufactured by Gunze Co. Ltd.). A UV irradiation device (high-pressure mercury UV lamp manufactured by Eyegraphics Co. Ltd.) was used at 1000 mJ / cm 2 The laminate was irradiated with ultraviolet rays 10 times and 80 times. This is equivalent to a cumulative light intensity of 10000mJ / cm 2 and 80000mJ / cm 2 Conditions. Then, the chromaticity L*, a*, and b* of the CIE standard were measured before and after the irradiation of ultraviolet rays. The measurement was performed using a spectrophotometer (U4100 manufactured by Hitachi High-Tech) in the transmission color tone measurement mode. Then, the color difference ΔE was calculated as described above.
[0120] F. Appearance after UV irradiation
[0121] Visually observe that the above cumulative light intensity reaches 80000mJ / cm 2 The appearance of the adhesive sheet after
[0122] [Table 3]
[0123]
[0124] [Table 4]
[0125]
[0126] The following insights are obtained based on Tables 3 and 4. As shown in Examples 1 to 5, by using a halogen-containing ultraviolet absorber as an ultraviolet absorber, the transmittance of light with a wavelength of 400nm is 25% or less, and the degradation of optical functional sheets such as dimming sheets due to ultraviolet rays can be suppressed. In addition, it can be seen that the transmittance of light with a wavelength of 420nm is 80% or more, and sufficient visible light transmittance can be obtained. In addition, it can be seen that due to the low haze rate, the reduction in visual recognition of the optical functional sheet can be suppressed. In these Examples 1 to 5, since ΔE is less than 1.0, the color change before and after ultraviolet irradiation cannot be visually confirmed.
[0127] In Example 4, the haze rate is slightly higher than that of Examples 1 to 3 and 5, and the appearance is slightly turbid, but in the opinion of the inventors, it is considered that there is no problem in practical use. As the reason for the slightly high haze rate, it is considered that only ultraviolet absorber A is used in Example 4, and its content is higher than that of Examples 1 to 3. On the other hand, in Example 5, only ultraviolet absorber B is used, and although the appearance is not bad, the transmittance of light with a wavelength of 400nm is slightly high, and the ultraviolet absorption performance is slightly low. Therefore, in order to suppress the reduction of appearance and improve the ultraviolet absorption performance, it is preferred to contain ultraviolet absorbers A and B in a well-balanced manner as in Examples 1 to 3.
[0128] In Comparative Example 4, only UV absorber A is used as a UV absorber, but due to the high content, the haze rate and chromaticity b* are high, and uneven white turbidity is also produced, and the appearance properties are reduced. On the other hand, in Comparative Example 5, only UV absorber B is used as a UV absorber, but due to the high content, although the UV absorption performance is high, it is precipitated on the surface of the adhesive sheet. In addition, the transmittance of light with a wavelength of 420nm is slightly reduced. Therefore, it can be seen that the upper limit of the content of UV absorbers A and B is preferably less than 9 parts by weight and less than 3 parts by weight, respectively, relative to 100 parts by weight of (meth) acrylate copolymer.
[0129] In Comparative Example 3, UV absorber C was used as the UV absorber, but since it did not contain a halogen group, the haze rate and chromaticity b* were high, and white turbidity unevenness also occurred. In addition, the transmittance of light with a wavelength of 400 nm was high, indicating that the UV absorption performance was low.
[0130] Comparative Example 1 contains no ultraviolet absorber and thus has almost no ultraviolet absorbing performance. Comparative Example 2 uses a benzophenone-based ultraviolet absorber as an ultraviolet absorber and has a white appearance and a high haze rate. As a result, the transmittance of light with a wavelength of 420 nm is slightly reduced.
[0131] Description of Reference Numerals
[0132] 2: Adhesive layer (adhesive sheet)
Claims
1. An adhesive sheet, which is an adhesive sheet for an optical functional member, The adhesive sheet includes: a (meth)acrylate copolymer as a main component, a crosslinking agent, and an ultraviolet absorber, At least one of ultraviolet absorber A and ultraviolet absorber B is contained as the ultraviolet absorber, When the ultraviolet absorber A is contained, its content is 9 parts by weight or less relative to 100 parts by weight of the (meth)acrylate copolymer, When the ultraviolet absorber B is contained, its content is 3 parts by weight or less relative to 100 parts by weight of the (meth)acrylate copolymer, The ultraviolet absorber A contains the compound represented by formula (1), and the ultraviolet absorber B contains the compound represented by formula (2), In the formula, R1, R4, and R5 represent lower alkyl groups having 1 to 6 carbon atoms, R2 represents a lower alkylene group having 1 to 6 carbon atoms, and R3 represents an alkyl group having 5 to 15 carbon atoms, 2. The adhesive sheet according to claim 1, wherein, Both the ultraviolet absorber A and the ultraviolet absorber B are contained as the ultraviolet absorber.
3. The adhesive sheet according to claim 2, wherein, The content of the ultraviolet absorber A is 6 parts by weight or less relative to 100 parts by weight of the (meth)acrylate copolymer. The content of the ultraviolet absorber B is 2 parts by weight or less based on 100 parts by weight of the (meth)acrylate copolymer.
4. The adhesive sheet according to claim 1 or 2, wherein, The spectral transmittance of the pressure-sensitive adhesive sheet with respect to light having a wavelength of 400 nm is 25% or less.
5. The adhesive sheet according to claim 1 or 2, wherein, The thickness of the adhesive sheet is 15 to 300 μm.
6. A dimming device, which includes: A glass plate; A dimming sheet; and The adhesive sheet according to claim 1 or 2, which is used to fix the dimming sheet to the glass plate.
